Pengaruh Independensi Auditor Terhadap Manajemen Laba untuk KAP Big 5 dan Non Big 5 - INTEN MEUTIA (The Indonesian Journal of Accounting Research, 2013)
This research examines the effect of auditor’s independence on the relationship between audit quality and earnings management. This research is different from prior research because it examines whether two auditor’s independence  measures: non audit-services and auditor’s tenure affect the relationship between audit quality and earnings management (which is measured by using absolute discretionary accruals). Audit quality is classified as prior research, that is Big sized and non-Big sized firms. A correlation analysis uses to determine the relationship between audit quality and absolute discretionary accruals. Further, auditor’s independence is used as a moderating variable to determine the effect of the relationship between the two other variables. Using  a sample  of 131 firms listed on the Jakarta Stock Exchange, in Indonesia  over the period 1998 to 2001, a significant negative relation between audit quality and absolute discretionary accruals was found.   This finding support the hypothesis and is consistent with result from prior research. Independent t-test is used to determine the effect of non audit services and auditor tenure. Both variables give significant effect on the relation between audit quality and absolute discretionary accruals.  The existence of non-audit services increases the value of absolute discretionary accruals both for Big and non-Big audit firms.  On the other hand, the long tenure decreases the value of absolute discretionary accruals both for Big and non-Big audit firms.